Creative clinical teaching in the health professions - Melrose, Sherri, 1951-; Park, Caroline, 1948-; Perry, Beth, 1957- (desLibris. Books collection., 2021)
"For healthcare professionals, clinical education is foundational to the learning process. However, balancing safe patient care with supportive learning opportunities for students can be challenging for instructors and the complex social context of clinical learning environments makes intentional teaching approaches essential. Clinical instructors require advanced teaching knowledge and skills as learners are often carrying out interventions on real people in unpredictable environments. Creative Clinical Teaching in the Health Professions is an indispensable guide for educators in the health professions. Interspersed with creative strategies and notes from the field by clinical teachers who offer practical suggestions, this volume equips healthcare educators with sound pedagogical theory. The authors focus on the importance of personal philosophies, resilience, and professional socialization while evaluating the current practices in clinical learning environments from technology to assessment and evaluation. This book provides instructors with the tools to influence both student success and the quality of care provided by future practitioners."--